Struktur ruang dan elemen persekitaran rumah Melayu Tradisi di Kelantan / Siti Norlizaiha Harun, Mohd Nasurudin Hasbullah and Azira Ibrahim - Harun, Siti Norlizaiha; Hasbullah, Mohd Nasurudin; Ibrahim, Azira (Universiti Teknologi MARA, Perak, 2011)
This research aims to identify the space structure of Malay traditional houses and environmental elements which form the character of traditional villages in Kelantan. Through this research, one of the values and tradition of the Malaya community has been detected, namely, societal norms in planning and layout of space activity. It is culture or behaviour which occurs in traditional Malay community which, all this while, has been perceived as one of the panorama of village landscape. Based on site survey, the space structure of the Malay traditional village house in Kelantan falls into two parts: the front and rear sections. The front sectionof the house is known as the compound. It is an open space that does not block the view from the main road. Features that are commonly seen in the compounds are non-grassy areas, fruit trees such as rambutan or mango planted in front of the house. There is also the wood bunk for retreat and and a well.